TUNING RANDOM EARLY DETECTION ROUTER MECHANISM FOR TCP-FRIENDLINESS (Journal of Information and Communication Technology, 2022)
The Internet Engineering Task Force (IETF) has strongly recommended the use of the Random Early Detection (RED) active queue management mechanism in network routers (gateways) for controlling Internet congestion. In this article, we describe our experiences with RED parameters from our study on how the TCP-friendliness property of a rate-based congestion control protocol is affected by different parameterizations of RED. We explore a range of optimal RED parameter values for ensuring the TCP-friendliness of competing network connections. Our experimental results show that different RED parameterization does affect the TCP-friendliness of rate-based control protocol. We also argue that an appropriate tuning of RED gateway can significantly improve the TCP-friendliness of rate-based congestion control protocol.